Escore prognóstico da Gastrosquise: impacto na evolução pós-operatória e na morbi-mortalidade. Estudo prospectivo. - Renan Farias Rolim Viana (2020)
INTRODUCTION: Gastroschisis is a congenital abdominal wall anomaly that exposes intestinal loops to amniotic fluid. Prenatal diagnosis makes possible adequate reference of these cases to a reference center. A new gastroschisis classification considers too the level of the associated serositis in order to evaluate outcomes of these newborns. This study intends to follow up newborns with gastroschisis for 4 years at a teaching hospital. OBJETIVES: To describe maternal and newborns profile that had a prenatal diagnosis of gastroschisis. Besides, it is intended to describe outcomes in accordance to the Gastroschisis Prognosis Score (GPS) and to surgical technique performed. Finally, to determine associated characteristics that could have impaired hospital length of stay. METHOD: After ethical approved form UFMG ethical board, a prospective study was realized to evaluate 61 newborns with gastroschisis, accordingly to pre-stablished protocol from 2015 to 2019. Data bank was built to save data regarding the following variables: maternal, patient’s profile, clinical-surgical treatment, complications and survival rates. Statistical analysis was done to find correlations between length of stay, GPS and modality of surgical intervention. RESULTS: Every mother has done prenatal ultrasonography. 59 (96,7%) of the children was born at HC-UFMG, c-section was the preferred modality in 53 (86,9%). 35 (57,4%) of the children was born within less 37 weeks of gestation and 9 (14,7%) had complex gastroschisis. Regarding GPS classification, 24 (39,34%) were classified into GPS <2 e 37 (60,65%) GPS ≥ 2. Considering the treatment variables, 34 (55,7%) children was ≤ 4 hours age in the moment of the operation; and 17 (27,9%) were submitted to staged repair. Average time of NPT need was 30 days and mechanical ventilation (VM) support was necessary in a mean of 10 days. Enteral feeding was introducing in 15 days, in average. Hospital length of stay ranged from 16 to 124 days, with a mean of 43 days. In view of complications, 42 (68,9%) patients had sepsis, 30 (49,2%) prolonged paralytics ileus, 4 (6,6%) necrotizing enterocolitis and 8 (13,1%) died. Multivariate statistical analysis demonstrated that: GPS ≥ 2 was correlated with surgical staged repair and lenght of VM ≥ 8 day; early discharge (≤ 30 days) was associated with the following indicators: GPS < 2, enteral feeding introducton within 10 days age and sepsis absence; children classified into GPS ≥ 2 had higher chances to present prolonged paralytics ileus. CONCLUSIONS: gastroschisis prenatal diagnosis provide early treatment of the newborns with this condition. GPS classification contributes to identify patients that will require prolonged neonatal intensive critical care. Patients with complex gastroschisis or high degree of serositis will face worse outcomes. This information is essential to provide adequate parenteral counseling and serve as guide to hospital logistics improvement and to Gastroschisis management protocols updates.